Avaliação da força muscular respiratória, função pulmonar e sintomas persistentes da COVID-19 após um ano da infecção: um estudo transversal - Rebouças, Ellys Rhaiara Nunes (2024)
Manifestations of COVID-19, even after the acute phase, in the form of sequelae and post-COVID-19 symptoms are common among those who have recovered. In addition to infection at a systemic level, the virus's predilection for lung tissue is evident, bringing considerable consequences to the respiratory system, which may result in the need for hospital admission. Therefore, it is necessary to investigate the respiratory repercussions and persistent symptoms presented by recovered individuals. the severe form of the disease. Objective: To evaluate respiratory muscle strength, lung function and persistent symptoms of COVID-19 one year after infection. Methods: Participants were recruited during hospitalization and, one year after hospital discharge, they underwent assessment of respiratory muscle strength and lung function, and answered a structured questionnaire about the persistence of post-COVID-19 symptoms. Results: 50 participants were evaluated, with a mean age of 54.86±17.87 years, 64% of whom were male. All (100%) showed changes on the CT scan upon admission. The most frequently reported persistent symptoms were respiratory (78%), neurological (60%) and musculoskeletal (54%). In manovacuometry, PImax (112.80±36.91) and PEmax (117.8±32.67) values were observed. In spirometry, the sample reached only 59.78% of the predicted FVC (3.27±0.88). Patients who had less than 50% impairment on CT, who did not require supplemental oxygen or IMV during hospitalization, presented worse results in the PEF assessment compared to those who had impairment greater than 50% (p=0.036). Those who did not require oxygen upon admission had low FVC (p=0.024) and FEV1 (p=0.024) values. Those who had worse CT findings (>50%) reported having undergone rehabilitation after hospitalization. One year after hospital discharge, patients who presented the less severe acute form of the disease had lower PEF, FVC and FEV1. Fatigue with minimal effort, muscle fatigue and memory loss were the most reported symptoms.